Rosyjskie odpowiedniki przekładowe polskiego predykatywu trzeba - Rudyk, Anna (Acta Polono-Ruthenica, 2018)
The article shows the Russian equivalents of the lexeme trzeba extracted from the contemporary Polish prose and its translation into Russian. The modal predicatives нужно and надо and the forms приходится and следует are the most frequent equivalents.